Embedded GaAs nanopillars studied by high resolution reciprocal space mapping and SEM. Issue 6 (20th May 2014) - Zozulya, Alexey V.; Slobodskyy, Taras; Bartsch, Thorben; Wetzel, Alina; Sonnenberg, David; Heyn, Christian; Sprung, Michael; Hansen, Wolfgang
<x xml:space="preserve">Abstract</x> Novel nanostructures based on GaAs nanopillars epitaxially embedded in air‐gap heterostructures have been studied by high resolution reciprocal space mapping using synchrotron radiation. The measurements were motivated by thermal conductance measurements on samples with different pillar densities that show unexpected behavior. X‐ray diffraction data and scanning electron microscopy (SEM) images were used to assess the quality of investigated heterostructures with different pillar densities. Our SEM studies reveal high quality of stripes and trenches in the air‐gap heterostructures. X‐ray diffraction profiles extracted from the measured reciprocal space maps confirm the homogeneous profile of air gaps. We found no indication of material contact between the top and the bottom layers of the air‐gap heterostructures due to sagging. In addition, the structural quality of the bulk and the top layers of heterostructures is addressed.